Description of Side Effects of Using Antituberculosis Drug in Pulmonary Tuberculosis Patients: Literature Review - Nisrina, Hasna; Hilmi, Indah Laily (Sean Institute, 2022)
Pulmonary tuberculosis (TB) is a chronic and infectious disease that is still a global concern. The bacterium that causes tuberculosis is the bacterium Mycobacterium tuberculosis. The high incidence of tuberculosis is due to the rapid spread of bacteria caused by the easy transmission of the disease, namely through the droplet nucleus containing Mycobacterium tuberculosis. Tuberculosis morbidity and mortality is a serious problems, especially due to the emergence of side effects of Anti Tuberculosis Drugs (OAT). most sufferers feel unable to tolerate the side effects of OAT experienced during the treatment process. This study aimed to determine the side effects felt by patients with pulmonary tuberculosis who used antituberculosis drugs. The most widely used method is the descriptive method with a cross-sectional approach with different data collection. The results showed that side complaints caused by OAT ranged from mild effects: nausea, abdominal pain, joint pain, tingling, and red urine to severe side effects, namely respiratory syndrome (shortness of breath), itching, and redness of the skin, deafness, jaundice. without other causes, visual disturbances, and vomiting.